Pengaruh Literasi Keuangan, Financial Technology, dan E-Commerce Terhadap Kinerja UMKM dengan Business Experience Sebagai Variabel Moderating - Riski Yama Lestari; Dewi Sartika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The growth of micro, small, and medium enterprises (MSMEs) in Indonesia has been increasing every year and needs to be enhanced through knowledge and experience. MSMEs play a significant role in supporting the country's economy, even though business success is low and exports are still minimal; nonetheless, MSMEs continue to contribute to the nation. The purpose of this research is to analyze the influence of financial literacy, financial technology, and e-commerce on the performance of MSMEs and how business experience moderates this effect. This research is quantitative in nature. Data collection was conducted using purposive sampling by distributing questionnaires filled out by 100 MSME actors in the Seberang Ulu II sub-district of Palembang City, who utilize financial technology and e-commerce. This study employs SEM-PLS 4 analysis method. The results of this study indicate that financial literacy, financial technology, and e-commerce have a positive and significant impact on the performance of MSMEs in the Seberang Ulu II Palembang City. Furthermore, the analysis results of the moderating variable show that business experience has a significant role in strengthening the relationship between financial literacy and financial technology on the performance of MSMEs, whereas business experience does not have a significant role in strengthening the relationship between e-commerce and the performance of MSMEs.